STUDENTS’ ERROR ANALYSIS IN CONSTRUCTING SIMPLE PAST TENSE OF THE EIGHTH GRADE STUDENTS AT SMP N 2 LIRUNG - Slarmanat, Gethereda; Tuna, Jim R.; Liando, Nihta V. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to identify students’ errors and dominant errors and examine the causes of errors students make in constructing simple past tense. The errors have been classified into four types: omission, addition, misformation, and misordering, based on the surface approach taxonomy from Dulay. The researchers used a descriptive quantitative method to find the result. The subject of this research was the eighth-grade students of SMP N 2 Lirung, which consists of 30 students. The instrument for gathering the data was the essay test. The findings showed that the students made 250 errors. With 170 errors or 68%, misformation is the most common error students commit. The addition comes in second with 30 errors, or 12%. The following error is an omission, with 28 errors totaling 11,2%, and misordering with 22 errors, or 8.8%. In addition, the cause of errors students made in constructing simple past tense is Carelessness, with a total number of 133 or 53.2%, followed by the first language with 75 or 30% errors, and the last cause of error, translation, with 42 or 16.8% errors. Misformation is the most frequent error that students of the eighth grade at SMP N 2 Lirung make when constructing simple past tense. The cause of errors students make in constructing simple past tense is Carelessness, followed by first language and translation. From the percentage of students, the mastery of using simple past tense was poor